2021
DOI: 10.1021/acs.jpclett.1c01739
|View full text |Cite
|
Sign up to set email alerts
|

Can Vacuum Deposition Apply to Bismuth-Doped γ-CsPbI3 Perovskite? Revealing the Role of Bi3+ in the Formation of Black Phase

Abstract: The B-site doped CsPbI3 has been demonstrated to be very promising for photovoltaics owing to its low black phase transition temperature. Though B-site doped black-CsPbI3 perovskites have been successfully achieved by solution-processing, it is unclear whether these systems are available by other methods such as vacuum deposition. In this work, heterovalent doped CsPb1–x Bi x I3 is targeted. To incorporate Bi3+ into the final film via vacuum deposition, the solid solution precursor Pb1–x Bi x I2 (0.01 ≤ x ≤ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…As the adjacent element to Pb in the periodic table, the trivalent Bi 3+ cation has a similar electronic configuration and ionic radius to Pb and Sn, and therefore has been used to partly substitute the Pb 2+ cation at the B sites of lead perovskites. 184,185,306 For example, in an earlier study, Bi 3+ doping of CsPbI 3 was reported to improve the performance of CsPbI 3 solar cells although a recent study found that the Bi 3+ doped CsPbI 3 is not a thermodynamically favored system despite its better tolerance factor. 185 Pure Bi 3+ -occupied B site, neutral perovskites with the formula ABX 3 (A = Cs, MA; X = I, Br, Cl) are not possible because of the +3 valence state.…”
Section: Bismuth Perovskite (Analog) Solar Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the adjacent element to Pb in the periodic table, the trivalent Bi 3+ cation has a similar electronic configuration and ionic radius to Pb and Sn, and therefore has been used to partly substitute the Pb 2+ cation at the B sites of lead perovskites. 184,185,306 For example, in an earlier study, Bi 3+ doping of CsPbI 3 was reported to improve the performance of CsPbI 3 solar cells although a recent study found that the Bi 3+ doped CsPbI 3 is not a thermodynamically favored system despite its better tolerance factor. 185 Pure Bi 3+ -occupied B site, neutral perovskites with the formula ABX 3 (A = Cs, MA; X = I, Br, Cl) are not possible because of the +3 valence state.…”
Section: Bismuth Perovskite (Analog) Solar Cellsmentioning
confidence: 99%
“…184,185,306 For example, in an earlier study, Bi 3+ doping of CsPbI 3 was reported to improve the performance of CsPbI 3 solar cells although a recent study found that the Bi 3+ doped CsPbI 3 is not a thermodynamically favored system despite its better tolerance factor. 185 Pure Bi 3+ -occupied B site, neutral perovskites with the formula ABX 3 (A = Cs, MA; X = I, Br, Cl) are not possible because of the +3 valence state. 306 Instead, CsPbI 3 forms ternary Bi 3+ -based perovskites that exist in structures with the formula A 3 Bi 2 X 9 (A = MA + , Cs + or Ag + , and X = I À or Br À ), where three Pb 2+ ions are replaced by two Bi 3+ ions to maintain the charge neutrality, and they form a 2D or 0D structure with face-sharing octahedra, unlike 3D CsPbI 3 or MAPbI 3 perovskite that exist in corner-sharing octahedra.…”
Section: Bismuth Perovskite (Analog) Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frolova et al fabricated a 2D heterojunction CsPbI 3 perovskite cell achieving a power conversion efficiency of 10.5%, which was very close to the CH 3 NH 3 PbI 3based solar cell at that time [18]. The black cubic phase CsPbI 3 with a band gap of 1.73 eV is suitable for use as an absorption layer in photovoltaic devices [19][20][21][22][23]. However, only when the temperature exceeds ∼300 • C can CsPbI 3 maintain the stable black phase, while it should turn into an insulating yellow quadrature phase just in a few minutes at room temperature [24].…”
Section: Introductionmentioning
confidence: 88%
“…Organic-inorganic halide perovskite solar cells have attracted wide attention due to their low cost, easy preparation and excellent photoelectric performance [1][2][3][4][5][6][7][8][9]. The conversion efficiency of single-junction perovskite solar cells has increased from 3.8% in 2009 to 25.7% in 2023 [10,11].…”
Section: Introductionmentioning
confidence: 99%